GAMBARAN KEBUTUHAN RAK DAN RUANG PENYIMPANAN DOKUMEN REKAM MEDIS DI RUMAH SAKIT TINGKAT III 03.06.01 CIREMAI - Dyah Ayu Lestari; MH Asiana Gabril YD; Riantina Luxiarti (LPPM ITEKES Mahardika, 2018)
Background :Supporting swiftness in storage and back the medical record document needed comformity of storage capacity the medical record document, it can be achieved by planing shelves and storage space. Purpose: The reseacher want to know the needs of shelves and storage space of medical record document at the Ciremai Hospital Tingkat III 03.06.01 Cirebon. Methods: The research method is descriptive qualitative.The population of research is 32.373 document and the sample is 376 document and then the sampling using an random sampling. Result : The result of research is average thickness of document is 0,5 cm so 1 shelves can accommodate 7.680 document, the needs of shelves 27, and needs storage space of 132 m2. Conclusion: The need of shelf storage of medical record document that is 27 shelves, currently the hospital already has 20 shelves and storage space document medical record is 132 m2, current wide storage space at home sickness is 59,62 m2 so that the storage space need the addition of room 72,38 m2.